Design and control of tensegrity morphing airfoils. (January 2020) - Chen, Muhao; Liu, Jiacheng; Skelton, Robert E.
Abstract: We present a general approach of design, dynamics, and control for tensegrity morphing airfoils. Firstly, based on reduced order Class- k tensegrity dynamics, a shape control law for tensegrity systems is derived. Then, we develop a method for discretizing continuous airfoil curves based on shape accuracy. This method is compared with conventional methods (i.e. evenly spacing and cosine spacing methods). A tensegrity topology for shape controllable airfoil is proposed. A morphing tensegrity airfoil example is given to demonstrate successful shape control. This work paves a road towards integrating structure and control design, the principles developed here can also be used for 3D morphing airfoil design and control of various kinds of tensegrity structures.